1995
DOI: 10.1126/science.7667639
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of Mip-1α for an Inflammatory Response to Viral Infection

Abstract: Macrophage inflammatory protein-1 alpha (MIP-1 alpha) is a chemokine that has pro-inflammatory and stem cell inhibitory activities in vitro. Its biologic role in vivo was examined in mice in which the gene encoding MIP-1 alpha had been disrupted. Homozygous MIP-1 alpha mutant (-/-) mice were resistant to Coxsackievirus-induced myocarditis seen in infected wild-type (+/+) mice. Influenza virus-infected -/- mice had reduced pneumonitis and delayed clearance of the virus compared with infected +/+ mice. The -/- m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

22
296
2
1

Year Published

1997
1997
2006
2006

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 591 publications
(321 citation statements)
references
References 14 publications
22
296
2
1
Order By: Relevance
“…Islet infiltration begins at 4 -6 wk of age in our colony of female NOD mice, and progression to destructive insulitis and overt diabetes occurs by 4 -6 mo of age. The incidence of diabetes in female NOD mice in our colony is 40 -50% at 15 wk of age and 80 -90% by 25 wk. C57BL/6J and 129/J mice were obtained from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Islet infiltration begins at 4 -6 wk of age in our colony of female NOD mice, and progression to destructive insulitis and overt diabetes occurs by 4 -6 mo of age. The incidence of diabetes in female NOD mice in our colony is 40 -50% at 15 wk of age and 80 -90% by 25 wk. C57BL/6J and 129/J mice were obtained from The Jackson Laboratory (Bar Harbor, ME).…”
Section: Methodsmentioning
confidence: 99%
“…Ϫ/Ϫ mice C57BL/6.MIP-1␣ Ϫ/Ϫ mice, previously shown to be resistant to virus-induced autoimmune inflammation, were generated in 129 embryonic stem cells by gene-targeted disruption (25). Mice were backcrossed six generations onto the NOD background (Ͼ98% NOD-like; Idd1-7, Idd10, Idd12, Idd14, and Idd15 positive) and intercrossed to generate mice with the NOD.MIP-1␣ Ϫ/Ϫ and NOD.MIP-1␣ ϩ/ϩ genotypes.…”
Section: Generation Of Nodmip-1␣mentioning
confidence: 99%
“…CCL3 -/-mice [54] were purchased from The Jackson Laboratory (Bar Harbor, ME). CCR1 -/-mice [12] and CCR5 -/-mice [55] were generated as described previously.…”
Section: Micementioning
confidence: 99%
“…MIP-1␣ is induced in patients with diverse inflammatory diseases, including bacterial sepsis (27,28), malaria (29), and interstitial lung diseases (30), and in vivo administration of MIP-1␣ to laboratory animals results in localized infiltration of monocytes (31)(32)(33). In animal models of infections, MIP-1␣ has been shown to play a critical role in the cellular recruitment and inflammatory response to coxsackie and influenza infections (34), endotoxemia (35), bacterial pneumonia (36), and cryptococcosis (37,38). Two previous studies have examined the expression of MIP-1␣ in response to Aspergillus species; one showed that rat alveolar macrophages express MIP-1␣ mRNA when exposed to A. fumigatus conidia in vitro (39), and another demonstrated that MIP-1␣ is induced in the lungs after intrapulmonary challenge with conidia (40).…”
Section: Macrophage Inflammatory Protein-1␣ Is a Critical Mediator Ofmentioning
confidence: 99%